2009
DOI: 10.1016/j.etap.2008.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of CCA-treated wood: A comparative study with As2O5 and CrO3 on mice

Abstract: O PDF relativo ao artigo que solicita, não se encontra disponível em Acesso Aberto. Motivos: O editor não permite o depósito e disponibilização em acesso aberto do PDF que solicita. Para consultar o documento deve aceder ao endereço do editor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Heavy metals can induce renal injury (Liu et al, ). The nephrotoxicity of metals was well‐described in previous studies (Matos et al, ; Liu et al, ). Pb induces tumors in different target organs but most commonly is associated with kidney cancers in rodents.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Heavy metals can induce renal injury (Liu et al, ). The nephrotoxicity of metals was well‐described in previous studies (Matos et al, ; Liu et al, ). Pb induces tumors in different target organs but most commonly is associated with kidney cancers in rodents.…”
Section: Introductionmentioning
confidence: 57%
“…It induces several unwanted pathological changes in tissues such as heart, brain, liver and kidney (Dewanjee et al, ). The cells of proximal tubules are the principally susceptible to toxic substances because of being the first renal epithelial cells exposed to these compounds (Matos et al, ). In this study, we determined mononuclear cell infiltration, tubular degeneration, fibrosis, dilatation of Bowmann's space, hemorrhage, glomerular lobulation, and glomerular atrophy in LN treated rat kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, PbActreated mice showed increase in plasma creatinine and urea levels, which may reflect the renal failure onset [30] . Kidney plays a major role in the clearance and biotransformation of metals [31] , and therefore is considered as a primary target organ for metals induced toxicity [32] . PbAC could increase blood urea by more than one mechanism, including enhancement of proteins catabolism, conversion of ammonia to urea by induction of arginase-enzyme synthesis [33] , and inhibition of amino acids incorporation in proteins [34] .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, chromium and arsenic analyses (ICP-MS and GFAAS) were used for evaluation. Acute tubular necrosis and the individual effects of those compounds were reported after administration of CCA solution (Matos et al, 2009a(Matos et al, , 2009b(Matos et al, , 2010.…”
Section: Inherent Toxicity Associated To Chemical Components In Ccamentioning
confidence: 99%